External polyacrylate-coating as alternative material for preparation of photopolymerized sol-gel monolithic column - Simas Vaz, Fernando Antonio; de Castro, Patricia Mendonca; Molina, Celso [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Polachini, Ferminio Cesar [UNESP]; Messaddeq, Younes [UNESP]; Nunes, Adriana Palombo; Leal de Oliveira, Marcone Augusto (Elsevier B.V., 2008)
Photopolymerized sol-gel monolithic columns for use in capillary electrochromatography were prepared in 125 mu m i.d. polyacrylate-coated fused-silica capillaries. The polyacrylate-coating, unlike the polyimide one, is transparent to the radiation used (approximate to 370 nm), and thus, no coating removal is necessary. This is a very important particularity since intrinsic capillary column characteristics, such as flexibility and mechanical resistance, are unchanged. A mixture containing metacryloxypropyltrimethoxysilane (MPTMS) as the polymeric precursor, hydrochloric acid as the catalyst, toluene as the porogen and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Irgacure 819) as the photoinitiator was irradiated at 370 nm for 20 min inside the capillaries to prepare the columns through sol-gel approach. The versatility and viability of the use of polyacrilate as a new capillary external coating were shown through preparation of two columns under different conditions, which were tested in electrochromatography for separation of standard mixture containing thiourea (marker compound), propylbenzene, phenanthrene and pyrene. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: electrochromatography; monolithic stationary phase; photopolymerization; sol-gel; polyacrylate-coating